Pengaruh Citra Restoran Terhadap Behavioral Intention Dengan Kepuasan Konsumen Sebagai Mediasi (Survei pada Wisatawan yang Berkunjung di Wisata Alam Kemuning Karanganyar) - Sulistya, Sulistya; Rohwiyati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2022)
This study aims to analyze (1) the significance of the effect of restaurant image on behavioral intention (2) the significance of the influence of restaurant image on consumer satisfaction (3) the significance of the influence of consumer satisfaction on behavioral intention (4) the influence of restaurant image on behavioral intention mediated by customer satisfaction. This study took place in the Kemuning Nature Tourism area, Karanganyar Regency. This study used a sample of 100 respondents with accidental sampling technique. The data analysis technique used path analysis, t test and Sobel test. The results of the study show that (1) Restaurant image has a significant effect on behavioral intention. (2) Restaurant image has a significant effect on customer satisfaction. (3) Consumer satisfaction has a significant effect on behavioral intention. (4) The influence of restaurant image on behavioral intention is mediated by customer satisfaction. The conclusion of this study is that all hypotheses are accepted